Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1038/sj.leu.2400676
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of vitamin D derivatives and granulocyte–macrophage colony-stimulating factor in leukaemic cell differentiation

Abstract: It will be inevitable that not all cells will respond to differen- enhanced efficacy in the treatment of certain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Consistent with previous reports, 33 GM-CSF alone showed a minor effect on HL-60 ( Figure 5a) and U937 (Figure 5b) differentiation, with maximal increase of NBT-positive cells (8-10%) at day 6. Interestingly, the percentage of NBT-positive cells in HL-60 cultured in the presence of both GM-CSF and SS was increased to 83% compared to 60% with SS alone (Figure 5a) or 90% with ATRA alone (Figure 4b).…”
Section: Ss-induced Differentiation Of Hl-60 and U937 Is Augmented Bysupporting
confidence: 80%
“…Consistent with previous reports, 33 GM-CSF alone showed a minor effect on HL-60 ( Figure 5a) and U937 (Figure 5b) differentiation, with maximal increase of NBT-positive cells (8-10%) at day 6. Interestingly, the percentage of NBT-positive cells in HL-60 cultured in the presence of both GM-CSF and SS was increased to 83% compared to 60% with SS alone (Figure 5a) or 90% with ATRA alone (Figure 4b).…”
Section: Ss-induced Differentiation Of Hl-60 and U937 Is Augmented Bysupporting
confidence: 80%
“…In the current study, induction of differentiation by lycopene was demonstrated by the development of the NADPH oxidase (as measured by NBT reduction), which represents one of the characteristic functions of mature monocytes and granulocytes, and by expression of CD14 antigen (30,43). The CD14 expression data suggest that lycopene can induce differentiation toward monocytes to some extent.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the phagocytotic activity of the cells, induction of superoxide production, expression of glycoprotein IIb/IIa, and the expression of enzymes like non-specific esterase (NSE) are enhanced when the cells are induced to differentiate. These markers have all been shown to be significantly up-regulated in response to treatment of leukaemia cells by vitamin D compounds in vitro with EB 1089 being more potent than 1α,25(OH) 2 D 3 [53,70,[119][120][121][122][123]. In a study using human HL-60 leukemia cells, induction of cell differentiation in response to 1α,25(OH) 2 D 3 and EB 1089 was demonstrated to be accompanied by upregulation of the p21 WAF1/CIP1 as well as a marked decrease of telomerase activity [70].…”
Section: Differentiationmentioning
confidence: 98%